Revisiting the Notion of ‘Combat Action’ in the Context of the War Crime of Attack against Protected Historical Monuments and Buildings - Kovács Péter (HUNGARIAN YEARBOOK OF INTERNATIONAL LAW AND EUROPEAN LAW, 2025)
A temple is the ‘house of God ‘and monuments are a very important part of the cultural, historical and national identity of the local population. UNESCO established the World Heritage List inventorying natural and man-made sites that are of paramount importance for mankind. The so called The Hague law and Geneva law related to the conduct of hostilities or to the protection of victims of armed conflicts contain special provision protecting these items from attack except when they are already being used for military purposes and contribute considerably to the military efforts of belligerents. The Rome Statute also contains special rules criminalizing the attack against such objects. However, the International Criminal Court (ICC) was confronted with challenges in those cases where the charge was brought for a crime that represented or contained inter alia the attack against this type of protected object. The paper seeks to shed light on the legal background of the doctrinal and jurisprudential controversy and endeavors to suggest an adequate solution.